1998
DOI: 10.1089/ten.1998.4.65
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Morphology and Function in Hepatocyte Spheroids: A Model of Tissue Self-Assembly

Abstract: Hepatocytes can self-assemble into spheroids, which express enhanced differentiated function and may provide an important tool in tissue engineering. This study examines cell junction components as hepatocytes form either monolayer or spheroid, and correlates morphological changes with cytochrome P-450 function. Rat hepatocytes were cultured on either high-density (1 fxg/cm 2 ) or low-density (1 ng/cm 2 ) fibronectin, which promotes monolayers or spheroids, respectively. Immunofluorescence demonstrates that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Hepatocellular morphogenesis and assembly have been well established to be critical to the functional performance of liver-derived cells in vitro (Hansen et al, 1998;Singhvi et al, 1994a;Torok et al, 2001;Yuasa et al, 1993). In this study, we offer a bidimensional approach to systematically obtain distinct cell morphogenetic and functional outcomes by manipulating both substrate mechanical compliance and substrate bioactivity (ligand concentration).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular morphogenesis and assembly have been well established to be critical to the functional performance of liver-derived cells in vitro (Hansen et al, 1998;Singhvi et al, 1994a;Torok et al, 2001;Yuasa et al, 1993). In this study, we offer a bidimensional approach to systematically obtain distinct cell morphogenetic and functional outcomes by manipulating both substrate mechanical compliance and substrate bioactivity (ligand concentration).…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm has been commonly observed for hepatocytes in vitro, particularly for culture systems that utilize diverse biophysical attributes to elicit markedly variant patterns of hepatocellular morphogenesis (Dispersio et al, 1991;Hamamoto et al, 1998;Hamilton et al, 2001;Hansen et al, 1994;Sawamoto and Takahashi, 1997;Singhvi et al, 1994a). Notably, hepatocyte cultures, biophysically induced to be 3D in nature, exhibit a compacted, spheroidal morphology and typically express elevated levels of liver-specific functions indicative of a highly differentiated state (Hamada et al, 1997;Hansen et al, 1998). This is in direct contrast to the levels of functional activity reported for cultures that have adopted a more 2D morphology (Baker et al, 2001;Hamamoto et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…37 Cell aggregate culture has been shown to enhance CM gene expression patterns, 22 increase the synthesis and release of ECM components, 26 and accelerate CM differentiation efficiency of embryonic stem cells 25 and liver stem cells. 23 Similarly, Albrecht et al found that chondrocyte matrix biosynthesis was dependent on cell cluster size, rather than overall cell density.…”
Section: Clause Et Almentioning
confidence: 99%
“…During this process, cells undergo significant environmental changes. The cells in spheroids resume cell-cell contacts, and survive and maintain liver-specific functions much longer and superior to cells cultured as monolayers [Landry et al, 1985;Lin et al, 1995;Lazar et al, 1995a;Juillerat et al, 1997;Hansen et al, 1998;Tzanakakis et al, 2001]. Liver spheroid culture, reported as early as the 1980s [Landry et al, 1985], was mainly employed in artificial liver studies [Lazar et al, 1995b;Hu et al, 1997].…”
mentioning
confidence: 99%
“…These include self-assembly [Peshwa et al, 1994;Hansen et al, 1998;Yamada et al, 2001], magnetic bar rotationmediated [Yagi et al, 1993], gyrotatory-mediated [Walker et al, 2000], spinner-mediated [Sakai et al, 1996], and foam pore-trapping [Iijima et al, 1998] methods, and entrapping in collagen gel [Hansen et al, 1998] or alginated beads [Khalil et al, 2001]. Whatever the culture method, the liver cells in preparing threedimensional spheroid cultures experience a common process: intact liver tissue !…”
mentioning
confidence: 99%